The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.nicl.2017.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture modulates the abnormal brainstem activity in migraine without aura patients

Abstract: Migraine is a common neurological disease with a high prevalence and unsatisfactory treatment options. The specific pathophysiological mechanisms of migraine remain unclear, which restricts the development of effective treatments for this prevalent disorder. The aims of this study were to 1) compare the spontaneous brain activity differences between Migraine without Aura (MwoA) patients and healthy controls (HCs), using amplitude of low-frequency fluctuations (ALFF) calculation method, and 2) explore how an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
108
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(112 citation statements)
references
References 65 publications
3
108
1
Order By: Relevance
“…Stimulation, both pain and pleasure, has been reported to elicit opioid release in the OFG [35]. A recent resting-state MRI study found increased regional brain activity in the OFG in migraineurs after verum acupuncture [36]. Furthermore, persistent orbitofrontal hypofunction was reported to be associated with medication overuse headache [37], and decreased gray matter of this region was predictive of poor response to treatment [38].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation, both pain and pleasure, has been reported to elicit opioid release in the OFG [35]. A recent resting-state MRI study found increased regional brain activity in the OFG in migraineurs after verum acupuncture [36]. Furthermore, persistent orbitofrontal hypofunction was reported to be associated with medication overuse headache [37], and decreased gray matter of this region was predictive of poor response to treatment [38].…”
Section: Discussionmentioning
confidence: 99%
“…It is confirmed by many studies that acupuncture activates the release of some pain suppressors, such as endorphins, in the central nervous system 24 25. Li et al have concluded that the impairment of the homoeostasis of the trigeminovascular nociceptive pathway was involved in the neural pathophysiology of migraines, and acupuncture could help to restore this imbalance 26. Yue et al have shown that electro-acupuncture exhibited the antidepressant effect and alleviated the hippocampal neuroinflammation 27.…”
Section: Introductionmentioning
confidence: 94%
“…Functional magnetic resonance imaging (fMRI) can reveal the functional changes of the brain, and improve our understanding about the central neurological mechanisms of acupuncture [19]. In recent years, fMRI has been applied to investigate the central regulation mechanisms of the acupuncture's effects [20][21][22]. Acupuncture and sham acupuncture have relatively different brain responses in the medial frontal cortex, periaqueductal gray and rostral ventromedial medulla during analgesia [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fMRI has been applied to investigate the central regulation mechanisms of the acupuncture's effects [20][21][22]. Acupuncture and sham acupuncture have relatively different brain responses in the medial frontal cortex, periaqueductal gray and rostral ventromedial medulla during analgesia [23,24]. Most clinical trials focus on evaluating abnormal brain activity triggered by the specific effect (acupuncture -sham acupuncture), while ignoring the modulation of nonspecific effect (sham acupuncture) on brain.…”
Section: Introductionmentioning
confidence: 99%